Effectiveness of etravirine-based therapy for treatment-experienced HIV-infected patients - Gloria Huerta García; José Antonio Mata-Marín; Juan Carlos Domínguez-Hermosillo; Marcelino Chavez-García; Marco Issac Banda-Lara; Nohemi Nuñez-Rodríguez; Javier Enrique Cruz-Herrera; Jorge Luis Sandoval-Ramírez; Alfredo Villagómez-Ruiz; Bulmaro Manjarrez-Tellez; Jesús Enrique Gaytan-Martínez (Journal of Infection in Developing Countries)
Introduction: Treatment options are limited for HIV-1-infected individuals who have received extensive previous antiretroviral therapy. ETV has shown significant clinical benefits in treatment-experienced HIV-1+ patients with antiretroviral resistance. The aim of this study was to evaluate the effectiveness of ETV plus optimized background regimen in real-life conditions in a cohort of highly HIV-1 antiretroviral-experienced patients. Methodology: Retrospective cohort of treatment-experienced HIV-1-infected adults with virological failure who started therapy with an ETV-containing regimen. The effectiveness was evaluated using HIV-1 RNA viral load and changes in CD4+ cell count after 48 weeks of treatment. Results: Forty-two patients ≥ 16 years of age were included; 74% were men, and the median age was 45 years (IQR 41–53). All participants had prior non-nucleoside reverse transcriptase inhibitor use (55% nevirapine, 83%, efavirenz, and 28% both). Baseline median HIV-1 RNA viral load was 15,598 copies/mL (IQR 2651–84,175) and CD4+ cell count was 276 cells/mL (IQR 155–436). After 48 weeks of treatment, 90.5% (95% CI 78–96) of patients had HIV-1 RNA viral load < 200 copies/mL and 76% (95% CI 61–86) had < 50 copies/mL. CD4+ cell counts increased from baseline to 48 weeks of treatment to a median of 407 cells/mL (IQR 242–579); p < 0.001. Virological outcome was associated with virological failure at baseline HIV-1 RNA viral load ≥100,000 copies/mL (OR 7.6; 95% CI 1.2–44.80; p = 0.025). Conclusions: Our study provides clinically important evidence of the effectiveness and safety of ETV in highly antiretroviral-experienced HIV-1-infected patients.